Analisis Penerapan Activity Based Costing Pada Harga Pokok Produksi “Kopi Tempat Kamu Pulang” - Prayitno, Keshena Muhammad; Herawan, Rian; Ijudin, Yahya; Nugraha, Pashya Ade; Suprana, Ahmad Jogi; S, Saridawati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyse and compare the determination of cost of goods produced in Micro, Small, and Small Enterprise at Kopi Tempat Kamu Pulang using the Activity Based Costing (ABC) method with traditional method used by the owner of Kopi Tempat Kamu Pulang. Data was obtained through direct interviews with the owner and baristas of Kopi Tempat Kamu Pulang, as well as direct observation of the production process. The analysis method used is descriptive quatitative. The result of the study show that the use of Activity Based Costing method in determining the cost of goods produced produces significant differences compared to the traditional method which only includes raw material costs. The cost of goods produced using the Activity Based Costing method tends to be higher because it includes activities from direct labor costs and activities from factory overhead costs. This causes the selling price obtained to be higher and reduce competitiveness in the market. Therefore, it is recommended that MSME players such as Kopi Tempat Kamu Pulang can re-evaluate the determination of the cost of goods produced to ensure the sustainability and profitability of their business..